Can composition and preheating improve infiltrant characteristics and penetrability in demineralized enamel? - Livia Aguilera GAGLIANONE; Carmem Silvia PFEIFER; Caroline MATHIAS; Regina Maria PUPPIN-RONTANI; Giselle Maria MARCHI (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The composition of infiltrants can influence their physical properties, viscosity and depth of penetration (DP). Strategies are used to increase the DP, such as the addition of diluents or the use of heat. This study aimed to evaluate the effect of preheating and composition on physical properties and DP of infiltrants in demineralized enamel. The groups were assigned, and the following experimental formulations were made: 25%BisEMA +75%TEGDMA; 25%BisEMA +65%TEGDMA +10%ethanol; 25%BisEMA +65%TEGDMA +10%HEMA; 100%TEGDMA; 90%TEGDMA +10%ethanol; 90%TEGDMA +10%HEMA. The samples were photoactivated at two temperatures (25°C and 55°C). Degree of conversion (DC) was performed using an infrared spectrophotometer. Elastic modulus (E), flexural strength (FS) and contact angle (CA) tests were also performed. The DP of an infiltrant in demineralized enamel was determined by confocal laser scanning microscopy (CLSM) using an indirect labeling technique. The data were analyzed by two-way ANOVA and Tukey's test. DC increased after preheating in all the groups; however, 90%TEGDMA+10%ethanol showed the lowest DC for both temperatures, and the lowest E. Preheating did not influence E or FS. The CA increased at 55°C for most groups, but decreased for groups containing HEMA. Temperature did not seem to influence DP, and Icon showed the lowest DP values. The 100%TEGDMA composition showed more homogeneous penetration, whereas Icon showed heterogeneous and superficial penetration. The preheating technique does not improve all properties in all the material compositions. The composition of a material can influence and improve its properties.